Preparation, characterization, and pharmacokinetics of tilmicosin‐ and florfenicol‐loaded hydrogenated castor oil‐solid lipid nanoparticles. Issue 3 (30th September 2016) - Ling, Z.; Yonghong, L.; Changqing, S.; Junfeng, L.; Li, Z.; Chunyu, J.; Xianqiang, L.
Abstract : To effectively control bovine mastitis, tilmicosin (TIL)‐ and florfenicol (FF)‐loaded solid lipid nanoparticles (SLN) with hydrogenated castor oil (HCO) were prepared by a hot homogenization and ultrasonication method. In vitro antibacterial activity, properties, and pharmacokinetics of the TIL‐FF‐SLN were studied. The results demonstrated that TIL and FF had a synergistic or additive antibacterial activity against Streptococcus dysgalactiae, Streptococcus uberis, and Streptococcus agalactiae . The size, polydispersity index, and zeta potential of nanoparticles were 289.1 ± 13.7 nm, 0.31 ± 0.05, and −26.7 ± 1.3 mV, respectively. The encapsulation efficiencies for TIL and FF were 62.3 ± 5.9% and 85.1 ± 5.2%, and the loading capacities for TIL and FF were 8.2 ± 0.6% and 3.3 ± 0.2%, respectively. The TIL‐FF‐SLN showed no irritation in the injection site and sustained release in vitro . After medication, TIL and FF could maintain about 0.1  μ g/mL for 122 and 6 h. Compared to the control solution, the SLN increased the area under the concentration–time curve (AUC0‐t ), elimination half‐life ( T ½ke ), and mean residence time (MRT) of TIL by 33.09‐, 23.29‐, and 37.53‐fold, and 1.69‐, 5.00‐, and 3.83‐fold for FF, respectively. These results of this exploratory study suggest that the HCO‐SLN could be a useful system for the delivery of TIL and FF for bovine mastitis therapy.